2020
DOI: 10.1101/2020.05.04.20090845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asthma and COVID-19 in children – a systematic review and call for data

Abstract: Rationale:Whether asthma constitutes a risk factor for COVID-19 is unclear. Methods:We performed a systematic literature search in three stages: First, we reviewed PubMed, EMBASE and CINAHL for systematic reviews of SARS-CoC-2 and COVID-19 in pediatric populations, and reviewed their primary articles; next, we searched PubMed for studies on COVID-19 or SARS-CoV-2 and asthma/wheeze, and evaluated whether the resulting studies included pediatric populations; lastly, we repeated the second search in BioRxiv.org a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(63 reference statements)
0
1
0
Order By: Relevance
“… 24 Our patient has mild extrinsic asthma, well control under aerosol therapy (salmeterol/fluticasone twice per day). Some studies found asthma as a risk factor for hospitalization and respiratory support 25 and others 26 , 27 did not find association. Moreover there are very few data in childhood and more studies are needed.…”
Section: Discussionmentioning
confidence: 96%
“… 24 Our patient has mild extrinsic asthma, well control under aerosol therapy (salmeterol/fluticasone twice per day). Some studies found asthma as a risk factor for hospitalization and respiratory support 25 and others 26 , 27 did not find association. Moreover there are very few data in childhood and more studies are needed.…”
Section: Discussionmentioning
confidence: 96%